Filipino and Indonesian Migrant Domestic Workers in Hong Kong: Their Life Courses in Migration. (May 2020) - Liao, Tim F.; Gan, Rebecca Yiqing
This article presents a portrayal of Filipino and Indonesian female domestic workers' life courses in migration, using the life history calendar data from the 2017 survey of migrant domestic workers in Hong Kong. Applying sequence analysis, we first analyzed migration trajectory features such as individual migration trajectories, duration spent in each state, and longitudinal diversity of state distributions. We found that Indonesian domestic workers, compared with their Filipino counterparts, are more diverse in their migration histories, indicating involvements in serial migration. We also conducted a cluster analysis of the domestic workers' migratory trajectories. The analysis yielded three meaningful clusters/types of migrant workers—those moved late in life, those who participated in serial migration, and those migrated directly from their home country to Hong Kong. Finally, we investigated the effect of a complex migration history on job satisfaction and the characteristics of membership in the three ideal-typical migration types among the domestic workers older than 39 years.